2019
DOI: 10.3390/hydrology6030082
|View full text |Cite
|
Sign up to set email alerts
|

Relative Effect of Location Alternatives on Urban Hydrology. The Case of Greater Port-Harcourt Watershed, Niger Delta

Abstract: Globally, cities in developing countries are urbanising at alarming rates, and a major concern to hydrologists and planners are the options that affect the hydrologic functioning of watersheds. Environmental impact assessment (EIA) has been recognised as a key sustainable development tool for mitigating the adverse impacts of planned developments, however, research has shown that planned developments can affect people and the environment significantly due to urban flooding that arises from increased paved surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Many studies have found that development location can significantly alter the magnitude of peak streamflows (Du, Shi, van Rompaey, & Wen, 2015; Yang, Bowling, Cherkauer, & Pijanowski, 2011; Yeo & Guldmann, 2006). Basin size, impervious surface connectivity, and flow timing have been found to have significant impacts on peak flow as well, which may explain the differing conclusions about which basin position is best for development (Dan‐Jumbo & Metzger, 2019; Du et al, 2015; Mejía & Moglen, 2010).…”
Section: Example 3: Plotting Land Use Distributions In Longitudinal S...mentioning
confidence: 99%
“…Many studies have found that development location can significantly alter the magnitude of peak streamflows (Du, Shi, van Rompaey, & Wen, 2015; Yang, Bowling, Cherkauer, & Pijanowski, 2011; Yeo & Guldmann, 2006). Basin size, impervious surface connectivity, and flow timing have been found to have significant impacts on peak flow as well, which may explain the differing conclusions about which basin position is best for development (Dan‐Jumbo & Metzger, 2019; Du et al, 2015; Mejía & Moglen, 2010).…”
Section: Example 3: Plotting Land Use Distributions In Longitudinal S...mentioning
confidence: 99%
“…Synthetic hydrographs provide an empiric representation of the response of small catchments to short and uniform rainfall events. Among them, the SCS hydrograph is one of the most widely used and cited models in specialised literature related to surface hydrology [36]. It is triangular and provides the basic hydrological parameters of a hydrograph.…”
Section: Transformationmentioning
confidence: 99%